De-identified survey response dataset for: "Multidisciplinary Exploratory Survey: Initial Insights into Biologic Drug Handling and Regulatory Perspectives Among Healthcare Professionals" - Sorret, Léa; Fuentes, Nathalie; Nonis, Lara; Damuzzo, Vera; Vozza, Giuliana; Paulsson, Mattias; De Paoli, Giorgia; Kwok, Stanley (Uppsala University, 2026)
This dataset contains de-identified responses from an exploratory cross-sectional survey on biologic drug handling, information sources, and regulatory perspectives among healthcare professionals (final analysed sample: n=35). The dataset includes one row per respondent and variables covering respondent category (professional role group) and broad geographic region, as well as coded answers to the 16 survey questions (Likert-scale items and multiple-choice responses).

Identifiers (e.g., names, email addresses, workplaces, free-text fields) have been removed. Geographic information and role categories are provided in aggregated form to reduce indirect identifiability.

The deposit includes: (1) the response dataset (CSV), (2) a data dictionary describing variable names, question wording, response options and coding, and (3) the survey instrument (PDF) as distributed. The files can be opened with standard spreadsheet software; no specialized software is required.

Denna datamängd innehåller avidentifierade svar från en explorativ tvärsnittsstudie om hantering av biologiska läkemedel, informationskällor och regulatoriska perspektiv bland hälso- och sjukvårdspersonal (slutligt analyserat urval: n=35). Data innehåller en rad per respondent och variabler som täcker svarskategori (yrkesrollsgrupp) och bred geografisk region, samt kodade svar på de 16 enkätfrågorna (Likert-skala och flervalsfrågor).

Identifierare (t.ex. namn, e-postadresser, arbetsplatser, fritextfält) har tagits bort. Geografisk information och yrkeskategorier ges i aggregerad form för att minska indirekt identifierbarhet.

Depositionen inkluderar: (1) svarsdatasetet (CSV), (2) en ”data dictionary” som beskriver variabelnamn, frågeformuleringar, svarsalternativ och kodning, och (3) undersökningsinstrumentet (PDF) som distribuerades. Filerna kan öppnas med standardprogramvara för kalkylblad; ingen specialiserad programvara krävs.
Keywords: INFORMATION MATERIALS; INFORMATIONSMATERIAL; DRUG THERAPY; LÄKEMEDELSTERAPI; Antibodies, Monoclonal; Monoklonala antikroppar; Drug Information Services; Läkemedelsinformation; Pharmacology; Farmakologi; Information Dissemination; Informationsspridning; Information Sources; Informationskällor; Pharmacist; apotekare; Ability to process information; förmåga att bearbeta information; Pharmaceutical Sciences; Farmaceutiska vetenskaper